2017
DOI: 10.1093/neuros/nyx225
|View full text |Cite
|
Sign up to set email alerts
|

Superior Prognostic Value of Cumulative Intracranial Tumor Volume Relative to Largest Intracranial Tumor Volume for Stereotactic Radiosurgery-Treated Brain Metastasis Patients

Abstract: BACKGROUND:Two intracranial tumor volume variables have been shown to prognosticate survival of stereotactic-radiosurgery-treated brain metastasis patients: the largest intracranial tumor volume (LITV) and the cumulative intracranial tumor volume (CITV). OBJECTIVE: To determine whether the prognostic value of the Scored Index for Radiosurgery (SIR) model can be improved by replacing one of its components-LITV-with CITV. METHODS:We compared LITV and CITV in terms of their survival prognostication using a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…[10] The overall survival patterns of these RCC patient cohorts were comparable in terms of median and 12-month survival (Table 1a). As such, these two cohorts were combined into a single cohort of 360 patients, with the goal of maximizing the statistical power of this “discovery” cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] The overall survival patterns of these RCC patient cohorts were comparable in terms of median and 12-month survival (Table 1a). As such, these two cohorts were combined into a single cohort of 360 patients, with the goal of maximizing the statistical power of this “discovery” cohort.…”
Section: Resultsmentioning
confidence: 99%
“…[7] The scale suggests that survival prognostication for RCC patients with BM is reliant on two clinical variables: Karnofsky’s Performance Score (KPS) and the number of BM. [7] Our previous work suggests that the Cumulative Intracranial Tumor Volume (CITV) of BM, defined as the sum volume of all intracranial metastases at the time of presentation, served as a strong prognostic factor for lung cancer patients afflicted with BM [810]. However, since the fundamental premise of dsGPA is that prognostic factors critical for each cancer type differ, it remains unclear whether CITV serve as an important prognostic factor in the context of RCC dsGPA.…”
Section: Introductionmentioning
confidence: 99%
“…While the use of SRS as a monotherapy has limitations, which include higher rates of salvage therapy, leptomeningeal disease, and distant tumor recurrences compared to WBRT, the overall survival and cost‐effectiveness of SRS alone vs SRS + WBRT favored SRS alone in two recent studies for up to 10 metastases . While one of the theoretical advantages of WBRT is its ability to treat multiple lesions at once, the data suggests that SRS is not limited by the number of lesions, but rather, the combined tumor volume (CTV) of the metastases, with WBRT favored only when the total tumor burden exceeds 5‐7 cm 3 . Indeed, Yamamoto et al showed no difference in treatment efficacy or toxicity in patients treated with SRS for 2‐9 vs >10 BM .…”
Section: Surgery For Newly Diagnosed Brain Metastasesmentioning
confidence: 99%
“…11 Also, Hirshman et al stated that cumulative intracranial tumor volume offers superior prognostic value relative to the largest intracranial tumor volume for SRStreated BM patients. 5 Serizawa et al reported that the post-SRS MST of patients with a cumulative tumor volume of 15 cm 3 or larger was significantly shorter than that of patients with a cumulative tumor volume less than 15 cm 3 . 16 Therefore, the addition of tumor numbers and cumulative tumor volume as scoring factors to the BSBM system is regarded as significantly improving the prognostic value of this index.…”
Section: Discussionmentioning
confidence: 99%